Assessment and intervention - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Advances in learning and behavioral disabilities, 2011)
The recent emphasis on accountability in policy and practice for individuals with learning and behavioral disabilities has placed a renewed focus on issues in assessment. However, assessment in itself is of little value unless it leads to more effective and systematic interventions. In this volume, a distinguished group of international authors provide important insights on recent advances on assessment and intervention, and the relation between the two. Included in this volume are chapters on curriculum based measurement and response to intervention, dynamic assessment and working memory, diagnostic accuracy and functional diagnosis, assessment of social behavior, assessment and intervention in reading and writing, assessment and treatment of attention deficit hyperactivity disorder, and assessment and intervention in social and emotional competence and self-determination. Taken together, these chapters provide significant new information that will be of interest to graduate students, clinicians, teachers, and other professionals concerned with effective assessment and intervention for individuals with learning and behavioral disabilities.